Immobilized Staphylococcus aureus phospholipase C on calcium alginate-chitosan: improved performance and industrial potential in soybean oil refining - Alzahrani, Areej Ali; Krayem, Najeh; Alonazi, Mona; Al-Shehri, Eman; Horchani, Habib; Ben Bacha, Abir (Frontiers in Bioengineering and Biotechnology, 2025)
Phospholipases are versatile biocatalysts with wide applications in the food and oil industries due to their ability to hydrolyze phospholipids and improve product quality. In this study, production of an extracellular phospholipase C from Staphylococcus aureus (PLCS.a) was optimized, purified, and its immobilization on calcium alginate-chitosan (CAC) was evaluated for soybean oil degumming. Statistical optimization significantly enhanced PLCS.a production, showing maximum yields during the exponential growth phase (232.5 U/mL at 34 h) and optimal activity at 37 °C and pH 7.5. Medium composition remarkably influenced enzymatic activity, with glucose (2%), bovine serum albumin (BSA, 1.5%), Tween 20/80 (0.5%–1%), and Zn2+/Ca2+ (0.1%–0.3%) identified as the most effective enhancers. Immobilization markedly improved enzyme stability, thermal and pH tolerance, and catalytic efficiency compared to the free form. PLCS.a exhibited broad substrate specificity, showing maximum activity toward phosphatidylcholine, and maintained activity in the presence of bile salts and divalent cations. Biotechnological application demonstrated efficient reduction of phosphorus levels in soybean oil from 198 mg/kg to below 2.5 mg/kg within 10 h. Reusability assessment showed that immobilized CAC-PLCS.a retained 100% activity for two cycles, 85.5% after five cycles, and 60% after nine cycles, confirming its operational stability. These results highlighted the potential of immobilized PLCS.a as a cost-effective, eco-friendly, and reusable biocatalyst for large-scale vegetable oil refining.